Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/adhm.201500156
|View full text |Cite
|
Sign up to set email alerts
|

A Processable Shape Memory Polymer System for Biomedical Applications

Abstract: Polyurethane shape memory polymers (SMPs) with tunable thermomechanical properties and advanced processing capabilities have been synthesized, characterized, and implemented in the design of a microactuator medical device prototype. The ability to manipulate glass transition temperature (Tg) and crosslink density in low-molecular weight aliphatic thermoplastic polyurethane SMPs is demonstrated using a synthetic approach that employs UV catalyzed thiol-ene “click” reactions to achieve post-polymerization crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The 4D shape‐changing behavior was achieved by deforming it in a small‐sized temporary shape in advance. Once triggered by an external stimulus such as water bath or infrared diode laser, the structure could recover and show self‐expanding behavior, as illustrated in Figure (d).…”
Section: Resultsmentioning
confidence: 99%
“…The 4D shape‐changing behavior was achieved by deforming it in a small‐sized temporary shape in advance. Once triggered by an external stimulus such as water bath or infrared diode laser, the structure could recover and show self‐expanding behavior, as illustrated in Figure (d).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, shape memory polyurethanes (SMPUs) have been widely studied as thermal‐induced shape memory polymers . By modifying their chemical composition, thermomechanical properties of SMPUs can be triggered for promising applications in biomedicine, automotive, aerospace, and also in textile sector .…”
Section: Introductionmentioning
confidence: 99%
“…This stent is thermally actuated and in vitro we accomplish this with heating the stent in a custom thermal chamber. Other in vitro methods that have been demonstrated to actuate endoluminal devices use an infrared diode laser or resistive heating . The most elegant approach, based on patient safety and efficacy, is Curie‐regulated inductive heating, which requires a ferromagnetic filler phase .…”
Section: Resultsmentioning
confidence: 99%
“…For that reason, while SMPs have generated much academic interest, engineering them in clinically useful form factors for biomedical devices has been challenging. Though multiple studies have reported proofs‐of‐concept for several thermally induced SMP devices, such as catheters, microgrippers, vascular stents, aneurysmal foams, orthodontic wires, and surgical sutures, the processing methods utilized to fabricate these devices were ad hoc and/or were used to obtain structures that are characterized by simple geometries. Melt stereolithography (SLA), in contrast, generates a 3D structure by sequentially UV polymerizing via a free radical mechanism molten (meth)acrylated resin, layer‐by‐layer.…”
Section: Introductionmentioning
confidence: 99%